Fall and rise of satellite repeats in allopolyploids of Nicotiana over c. 5 million years - Koukalova, Blazena; Moraes, Ana Paula; Renny-Byfield, Simon; Matyasek, Roman; Leitch, Andrew Rowland; Kovarik, Ales (The New phytologist, 2010)
Allopolyploids represent natural experiments in which DNA sequences from different species are combined into a single nucleus and then coevolve, enabling us to follow the parental genomes, their interactions and evolution over time. Here, we examine the fate of satellite DNA over 5 million yr of divergence in plant genus Nicotiana (family Solanaceae). We isolated subtelomeric, tandemly repeated satellite DNA from Nicotiana diploid and allopolyploid species and analysed patterns of inheritance and divergence by sequence analysis, Southern blot hybridization and fluorescent in situ hybridization (FISH). We observed that parental satellite sequences redistribute around the genome in allopolyploids of Nicotiana section Polydicliae, formed c. 1 million yr ago (Mya), and that new satellite repeats evolved and amplified in section Repandae, which was formed c. 5 Mya. In some cases that process involved the complete replacement of parental satellite sequences. The rate of satellite repeat replacement is faster than theoretical predictions assuming the mechanism involved is unequal recombination and crossing-over. Instead we propose that this mechanism occurs with the deletion of large chromatin blocks and reamplification, perhaps via rolling circle replication.
Keywords: druhová specificita; polymerázová řetězová reakce; hybridizace in situ fluorescenční; fylogeneze; Cloning, Molecular; Southernův blotting; Phylogeny; klonování DNA; Repetitive Sequences, Nucleic Acid; Species Specificity; Inheritance Patterns; Time Factors; satelitní DNA; typy dědičnosti; Nicotiana; DNA, Satellite; časové faktory; Diploidy; repetitivní sekvence nukleových kyselin; In Situ Hybridization, Fluorescence; Polymerase Chain Reaction; Polyploidy; Blotting, Southern; diploidie; tabák; polyploidie